2015
DOI: 10.1371/journal.pone.0123911
|View full text |Cite
|
Sign up to set email alerts
|

Caste-Specific Differences in Hindgut Microbial Communities of Honey Bees (Apis mellifera)

Abstract: Host-symbiont dynamics are known to influence host phenotype, but their role in social behavior has yet to be investigated. Variation in life history across honey bee (Apis mellifera) castes may influence community composition of gut symbionts, which may in turn influence caste phenotypes. We investigated the relationship between host-symbiont dynamics and social behavior by characterizing the hindgut microbiome among distinct honey bee castes: queens, males and two types of workers, nurses and foragers. Despi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
142
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(150 citation statements)
references
References 57 publications
6
142
0
2
Order By: Relevance
“…Both Lactobacillus and Bifidobacteriaceae are thought to be associated with processing complex carbohydrates and maintaining bee health (e.g., Forsgren et al 2010;Koch and Schmid-Hempel 2011a;Engel et al 2012;Mattila et al 2012;Vásquez et al 2012;Bottacini et al 2012;Koch and Schmid-Hempel 2012;Lee et al 2015;Ellegaard et al 2015;Moran 2015;Kwong and Moran 2016). In accordance with the results found here, a higher relative abundance of Lactobacillus species was found in non-age matched nurses versus foragers in previous work (Kapheim et al 2015). Further, it has been suggested that lactic acid bacteria (including Lactobacillus) play a beneficial role in protection against pathogens in honey bees (Forsgren et al 2010;Vásquez et al 2012).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Both Lactobacillus and Bifidobacteriaceae are thought to be associated with processing complex carbohydrates and maintaining bee health (e.g., Forsgren et al 2010;Koch and Schmid-Hempel 2011a;Engel et al 2012;Mattila et al 2012;Vásquez et al 2012;Bottacini et al 2012;Koch and Schmid-Hempel 2012;Lee et al 2015;Ellegaard et al 2015;Moran 2015;Kwong and Moran 2016). In accordance with the results found here, a higher relative abundance of Lactobacillus species was found in non-age matched nurses versus foragers in previous work (Kapheim et al 2015). Further, it has been suggested that lactic acid bacteria (including Lactobacillus) play a beneficial role in protection against pathogens in honey bees (Forsgren et al 2010;Vásquez et al 2012).…”
Section: Discussionsupporting
confidence: 90%
“…Gut bacterial communities and behavioural phenotype in worker bees may be influenced by many of the same characteristics, e.g., diet and environment (e.g., division of labour reviewed in Johnson 2010; the bee microbiome reviewed in Engel et al 2016). This means there is likely a link between behavioural phenotype and gut bacterial community, but to date this has been little explored (but see Kapheim et al 2015).…”
mentioning
confidence: 99%
“…In the second experiment, we observed a large number of non-core bacteria, particularly P. apium , non-Firm 4 and Firm 5 Lactobacillus sp., Enterococcaceae , and the pathogen P. larvae . P. apium is found at lower levels in the gut (Corby-Harris et al 2014a;Martinson et al 2011;Martinson et al 2012;Moran et al 2012;Sabree et al 2012) and is typically more abundant in hive food stores (Anderson et al 2014), queens (Kapheim et al 2015;Tarpy et al 2015), larvae (Vojvodic et al 2013), and in the hypopharyngeal glands and crops of nurses (Corby-Harris et al 2014b). Because P. apium is relatively abundant in food stores, hypopharyngeal glands, and crop, one possibility is that the guts displaying high P. apium titers were recently inoculated through either pollen feeding or trophallaxis.…”
Section: Discussionmentioning
confidence: 99%
“…Smaller numbers of bacteria, often representing environmental species, occur in the foregut and midgut [3]. The core species are relatively infrequent in larvae and in adult queens, which contain highly variable communities dominated by environmental bacteria [4, 5]. The mature worker hindgut microbiome is substantial, totaling 10 8 –10 9 bacterial cells [6] and is established in workers within four days following eclosure, before leaving the hive.…”
Section: The Gut Microbiome Of Corbiculate Beesmentioning
confidence: 99%